2004
DOI: 10.1073/pnas.0306433101
|View full text |Cite
|
Sign up to set email alerts
|

Microsecond folding dynamics of the F13W G29A mutant of the B domain of staphylococcal protein A by laser-induced temperature jump

Abstract: The small size (58 residues) and simple structure of the B domain of staphylococcal protein A (BdpA) have led to this domain being a paradigm for theoretical studies of folding. Experimental studies of the folding of BdpA have been limited by the rapidity of its folding kinetics. We report the folding kinetics of a fluorescent mutant of BdpA (G29A F13W), named F13W*, using nanosecond laser-induced temperature jump experiments. Automation of the apparatus has permitted large data sets to be acquired that provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 39 publications
4
88
0
Order By: Relevance
“…For example, at 25°C, the enthalpic folding barrier ⌬H ‡ϪD (in the original notation) Ϸ30 kJ⅐mol Ϫ1 for chymotrypsin inhibitor 2 (CI2) (11) and Ϸ32 kJ⅐mol Ϫ1 for cold shock protein CspB (12); but the enthalpy peak is only Ϸ7.5 kJ⅐mol Ϫ1 for three-methane association at room temperature (21). A recent simulation of protein A (38) found that the enthalpy change from an unfolded to a transition regime is negative at the transition temperature, consistent with experiment (14), but conditions corresponding to lower experimental temperatures with positive enthalpic folding barriers were not explored. Here, Fig.…”
Section: Ramifications For the Transition States Of Protein Foldingmentioning
confidence: 65%
See 1 more Smart Citation
“…For example, at 25°C, the enthalpic folding barrier ⌬H ‡ϪD (in the original notation) Ϸ30 kJ⅐mol Ϫ1 for chymotrypsin inhibitor 2 (CI2) (11) and Ϸ32 kJ⅐mol Ϫ1 for cold shock protein CspB (12); but the enthalpy peak is only Ϸ7.5 kJ⅐mol Ϫ1 for three-methane association at room temperature (21). A recent simulation of protein A (38) found that the enthalpy change from an unfolded to a transition regime is negative at the transition temperature, consistent with experiment (14), but conditions corresponding to lower experimental temperatures with positive enthalpic folding barriers were not explored. Here, Fig.…”
Section: Ramifications For the Transition States Of Protein Foldingmentioning
confidence: 65%
“…This picture is readily reconcilable with the empirical folding barriers along onedimensional free-energy profiles in traditional macroscopic descriptions (8) if the barriers arose solely from a reduction in conformational entropy during folding, because restriction on conformational freedom appears, by definition, as decrease in multidimensional surface area, rather than as barriers, on the microscopic free-energy landscape (6,9). However, experiments indicate a significant enthalpic component in empirical folding barriers (10)(11)(12)(13)(14). Our interest in high enthalpic folding barriers is motivated by two physical questions: (i) How does the existence of these barriers impact the folding funnel concept?…”
mentioning
confidence: 94%
“…Other ultra-fast folding proteins have been analyzed successfully in terms of a two-state process (22,23), implying that barrier crossing reaction is an appropriate description for these systems as well. Generally, proteins fold cooperatively, either at the global, domain, or subglobal level (24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…Single-molecule experiments can give conclusive answers. The B domain of Protein A (BDPA) is an ultrafast folding protein (17,36,37). Its refolding rate constant at 298 K in water is 10 5 s Ϫ1 (24).…”
Section: Resultsmentioning
confidence: 99%